2017
DOI: 10.3920/jiff2016.0032
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the use of insect-derived materials in Scottish salmon feeds

Abstract: Fishmeal is an important source of high quality protein in aquaculture, but concerns about its cost 13 and sustainability are making it a less attractive feed material. Replacing fishmeal with plant pro-14 teins can impact on the nutritional quality of farmed salmon. In theory insect meals could be substi-15 tuted for fishmeal without affecting the quality of the fish produced. They could also provide a way 16 of adding value to the bio-wastes used to rear the insects. However little is known about consumer 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 9 publications
4
56
0
Order By: Relevance
“…The use of insect meal in fish feed responds to such requirements, and recent research has shown a satisfactory level of its acceptance [30,37,[51][52][53][54]. In this study, we did not simulate the economic effects related to a possible fish price increase derived from the introduction of insect meal due to the lack of empirical evidence that confirms this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The use of insect meal in fish feed responds to such requirements, and recent research has shown a satisfactory level of its acceptance [30,37,[51][52][53][54]. In this study, we did not simulate the economic effects related to a possible fish price increase derived from the introduction of insect meal due to the lack of empirical evidence that confirms this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…; Popoff et al. ; Shepherd et al. ), raw materials derived from genetically modified organisms (Lucht ), and so on?…”
Section: More Than Nutrients and Ingredients: The Influence And Constmentioning
confidence: 99%
“…How does the composition of the diet influence the quality and nutritional value of the edible tissues (Fry et al 2016;Sprague et al 2016)? How do consumers view the use of traditional versus alternative ingredients (Mancuso et al 2016;Popoff et al 2017;Shepherd et al 2017), raw materials derived from genetically modified organisms (Lucht 2015), and so on? Nutritionists are understandably preoccupied with the nutritional aspects of feed formulation, but these other questions also merit their attention.…”
Section: More Than Nutrients and Ingredients: The Influence And Constmentioning
confidence: 99%
“…To enhance farmer uptake of the innovative technology and WTP for more sustainable and readily available alternatives such as IBF, improvements in extension support services are of paramount importance [4,39]. We therefore recommend the following: First, there is a need to increase farmer's knowledge on the nutritional value of insects, especially the BSF, as well as their use as alternative feed ingredients.…”
Section: Plos Onementioning
confidence: 99%
“…insects as feed, all in European countries including Belgium [33], France [34], Germany [35], Poland [36], Italy [37,38] and the United Kingdom [39]. Overall, these studies found a favourable attitude and willingness to accept insects in animal feed and resulting products from animals fed with IBF among respondents.…”
Section: Introductionmentioning
confidence: 99%